Improvement in strength properties of ash bricks by bacterial calcite - Dhami, N.; Reddy, M.; Mukherjee, Abhijit (Elsevier BV, 2012)
Carbonates are one of the most well known minerals that bacteria deposit by the phenomenon called microbiologically induced calcite precipitation (MICP). Such deposits have recently emerged as promising binders for protecting and consolidating various building materials. In the present study, we investigated the potential of Bacillus megaterium to produce calcite and improve properties of ash bricks (Fly ash bricks and Rice husk ash bricks). The treated bricks showed significant reduction in water absorption, better frost resistance and increased compressive strength due to calcite deposition on the surface and voids of bricks. Scanning electron micrographs revealed extracellular deposition of calcite crystals by the bacteria on the surface of the bricks. X-ray diffraction and energy dispersive X-ray analysis confirmed the precipitates formed as CaCO 3 are calcite crystals